Um estudo sobre os desafios da mulher no setor bancário - Rissi, Monica Tairine (2023)
The female participation in leadership in the adverse economic and financial sectors is being increasingly present, in which the research aims to present the challenges in the female career in companies inserted in the banking sector. As for the methodology, the nature of the research is applied, objective of analyzing the career challenges faced by women in several banks of the municipalities of Chapada and Almirante Tamandaré do Sul do Rio Grande do Sul through the application of a structured interview. The results obtained with the interviewees indicate that to gain respect and obtain a different perspective in different scenarios and positions of some clients and managers, women always have to demonstrate high knowledge and negotiation skills. However, women who have the same opportunities as men, depend on the posture adopted and their performance to conquer the desired positions, as well as being prepared for the possible changes in cities among other challenges that leadership positions require of the employee